Revisiting Slave Narratives II Les avatars contemporains des récits d'esclaves II - Misrahi-Barak, Judith (Horizons anglophones, 2007)
This collection offers a follow up to the first collection of essays Revisiting Slave Narratives / Les Avatars des récits d'esclaves (2005), whose purpose was to bring together African-merican and Caribbean neo-slave novels. In 2007, the year of the bicentennial anniversary of the official abolition of the transatlantic slave trade in the British colonial Empire, the memorialisation and commemoration events should not obliterate the fact that, through the prison of slave narratives and neo-slave novels, it is our present that is at stake. In order to show how our societies and minds still need to be manumitted, the essays in this collection examine books of fiction by André Brink, Octavia Butler, Barbara Chase-Riboud, Cristina Garcia, Edward P. Jones, Paule Marshall, Phyllis Perry, Susan Straight, and books of non-fiction by Malcom X or John Edgar Wideman ; as well as works by poets like Fred D'Aguiar or Marilyn Nelson, by playwrights like Robbie Mc Cauley, Derek Walcott or August Wilson, and by visual artists like David Boxer, Christopher Cozier, Glenn Ligon, or Kara Walker.